The presence of Silene cephalantha Boiss. (Caryophyllaceae) in Turkey - (:unkn) unknown (My University, 2007)
In this paper, the presence of Silene cephalantha Boiss. (Caryophyllaceae) is confirmed.
Keywords: Caryophyllaceae; Flora of Turkey; Silene cephalantha